2020
DOI: 10.1177/2152656720918874
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Hematopoiesis in the Sinonasal Cavity: A Case Report and Review of the Literature

Abstract: Background Extramedullary hematopoiesis (EMH) occurs in patients with hematologic disorders, but rarely within the paranasal sinuses. We report a case of EMH in a 17-year-old male with sickle cell disease (SCD) who presented with occipital pain and sinusitis. A computed tomography (CT) scan demonstrated heterogeneous opacification of the right maxillary sinus concerning for allergic fungal sinusitis or a fungal ball with bony erosion. He was taken to the operating room for endoscopic biopsy and a limited endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Common sites of EMH include the reticuloendothelial system such as spleen, lymph node, and mediastinum; however, the process can include virtually any tissue of the body [5]. Cases have been reported of EMH in the bowel, breast, pleura, and brain [6]. In our literature review, we found cases of retroperitoneal EMH after thalassemia and hereditary spherocytosis [7].…”
Section: Discussionmentioning
confidence: 78%
“…Common sites of EMH include the reticuloendothelial system such as spleen, lymph node, and mediastinum; however, the process can include virtually any tissue of the body [5]. Cases have been reported of EMH in the bowel, breast, pleura, and brain [6]. In our literature review, we found cases of retroperitoneal EMH after thalassemia and hereditary spherocytosis [7].…”
Section: Discussionmentioning
confidence: 78%
“…Any sinus can theoretically be affected, but the most commonly affected location was the maxillary sinus. There were 9 cases with maxillary involvement, 6 with sphenoid involvement, and 4 with ethmoid involvement [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Extraosseous and paraosseous EMH are the two forms of EMH [ 20 ]. Extraosseous haematopoiesis occurs in organs containing multipotent stem cells, such as the spleen and liver, and produces haematopoietic foci that are not associated with bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Splenomegaly or hepatomegaly, which can present as early satiety, bloating, pressure, or stomach discomfort, is common in patients. Para osseous EMH, in contrast to extraosseous EMH, arises surrounding the bone as a result of hyperactive marrow herniation [ 20 ]. It is more evidently seen in Sickle cell anaemia and thalassaemia as the erythroid marrow turnover is faster.…”
Section: Discussionmentioning
confidence: 99%